A Detailed Analysis of Microgrids - V. Bharathi; M. Arunachalam (Advanced Aspects of Engineering Research Vol. 13, 2021)
A microgrid is a set of linked loads and distributed energy resources that act as a single unit in relation to the grid within a clearly defined electrical boundary. A microgrid linked to distributed energy resources (DER) has proven to be a viable alternative to fossil fuels such as coal for generating electricity. Microgrids have paved the way for their perforation in a network of electrical components because of the associated comfort. Integrating the micro grid with the power grid presents many problems and concerns. Research is underway to address issues such as microgrid architecture, control techniques, and operating modes such as grid connected or islanded mode. This paper expands on previous research on microgrid issues and provides information on solutions proposed by researchers in areas such as microgrid design, operation, and control, distributed energy resources (DER), microgrid controllers, converters, energy storage, and security, as well as challenges that have yet to be addressed.